Analyzing By.U’s #CumaKamuYangBisa Digital PR Campaign in Building Generation Z Brand Awareness on TikTok - Sapta Aprilia; Lelita Azaria Rahmadiva (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Generation Z increasingly perceives brands as symbolic identities rather than mere providers of products or services, pushing telecommunications companies to move beyond price competition and adopt narrative-driven digital PR strategies on platforms such as TikTok. This research investigates the construction of messages in the By.U Provider digital PR campaign #CumaKamuYangBisa on TikTok. It employs Roland Barthes' semiotic framework to analyze its implications for enhancing brand awareness among Generation Z. Methodology: The study adopts a descriptive qualitative approach, applying Barthes' three layers of meaning in semiotic analysis, namely denotation, connotation, and myth. This Research analyze 11 videos from the #CumaKamuYangBisa digital PR campaign published by @by.u account on TikTok in August 2023. The analysis focus on four message elements: message theme, language style, emotional tone, and visual elements. Results: The digital PR campaign shows a progressive message theme that transitioned from product introduction to emotional integration. It employed an authentic language style resonating with Gen Z communication codes, showcased a variety of emotional tones ranging from comedic to dramatic, and maintained visual consistency through a light blue color palette. The application of Barthes' three layers of meaning indicates that the campaign constructs the brand myth of "a friend who understands Gen Z's digital identity." Applications/Originality/Value: This research addresses a gap in the literature by integrating Barthes' semiotics into the analysis of digital PR campaigns conducted by telecommunications providers on the TikTok platform, an area that remains relatively underexplored in Indonesian digital communication studies.